2003
DOI: 10.1207/s15327914nc4502_03
|View full text |Cite
|
Sign up to set email alerts
|

No Preventive Effect of Dietary Fiber Against Colon Cancer in the Japanese Population: A Cross-Sectional Analysis

Abstract: The report of Fuchs et al. in 1999 on the protective effects of dietary fiber (DF) against colon carcinogenesis has led many researchers to question the benefits of DF. We analyzed the relationship between dietary intake and mortality from colon cancer in Japan cross-sectionally. Dietary data were taken from the National Nutrition Survey. The standardized mortality ratio (SMR) was calculated using data from "Vital Statistics" and "the Population Census in Japan." Multiple regression analysis (stepwise variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This study was sponsored by the manufacturer of the fiber product (Madaus Laboratories, Cologne, Germany) . Another prospective follow‐up study from Japan found no association between fiber consumption and CRC mortality . This study had a longer follow‐up time than the 5‐year Spanish study …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…This study was sponsored by the manufacturer of the fiber product (Madaus Laboratories, Cologne, Germany) . Another prospective follow‐up study from Japan found no association between fiber consumption and CRC mortality . This study had a longer follow‐up time than the 5‐year Spanish study …”
Section: Resultsmentioning
confidence: 97%
“…Five studies examined the influence of dietary factors on outcome in CRC patients, which are referred to as survival studies . The remaining 11 studies investigated the influence of dietary factors on CRC outcome in the general population, which were referred to as mortality studies …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations